Social Characterization of Learning Assessment Supported by Virtual Environments (Autonomy, Learning to Learn, and Competencies) in the School of Exact and Natural Sciences (UNED) - Calderón Badilla, Yency (2020)
With the purpose of generating a social characterization of the evaluation of learning supported in virtual environments in the School of Exact and Natural Science of the Distance State University of Costa Rica, a research was proposed with a qualitative and comparative approach of three thematic variables: autonomy, the ability of learning to learn, and the development of competences of students in their learning process. Thirty-five people from five majors participated in group sessions and in-depth interviews. From the analysis of the categories studied, students’ decision making is observed in the resolution and organization of assessment tasks, especially to develop abilities to learn beyond their life as students. Likewise, pedagogical mediation was one of the most important aspects of motivation for the students, an aspect to be considered in the planning of virtual environments. On the other hand, the participants agreed that intellectual, social, personal, and professional competences are generated, such as the use of technology, the capacity for organization and planning, written communication, information management, commitment to learning, and the generation of knowledge for society.